TAHLIL AL-AKHTA’ AN-NUTHQIYYAH FI TA’DIYATI NABR AL-KALIMAH LADA THULAB AL MUSTAWAL AWAL BI JAMI’ATI ALI BIN ABI THALIB SURABAYA - Iqbal Gogari; Nasaruddin Nasaruddin; Musta'in Musta'in; Budi Santoso (Universitas Islam Negeri Mataram, 2024)
This research aims to explore the characteristics of phonetic errors in stress pronunciation among first-year students in the Arabic Language Department at the Faculty of Education and Teaching, Ali bin Abi Talib Islamic University, Surabaya, for the academic year 2023/2024. The researcher employs an error analysis method, with data focusing on recorded pronunciation errors by first-year students at Ali bin Abi Talib Islamic University in Surabaya. The approach used in the research is qualitative, specifically descriptive-analytical, where the study describes the phenomenon of phonetic errors in stress pronunciation made by students. The data type consists of linguistic errors found in the works of students from Ali bin Abi Talib Islamic University in Surabaya. The results indicate that first-year students were either inattentive to sentence correctness, rushed in their speech, or lacked knowledge about stress in Arabic language studies. For these reasons, the researcher investigates this issue to reveal what has been overlooked regarding the errors of students at Ali bin Abi Talib Islamic University, Surabaya, in the academic year 2023/2024, and so forth.